“Are darker individuals in control?”: A path model of the Dark Triad, Emotional Regulation and Locus of Control - Baptista, Makilim Nunes; Veiga, Cauany Ribeiro da; Cardoso, Hugo Ferrari; Bonfá-Araujo, Bruno (Studia Psychologica: Theoria et praxis, 2024)
Among the socially aversive personality traits, the Dark Triad (i.e., Machiavellianism, narcissism, and psychopathy) is one of the most prominent. It is known that there is an association between these traits and emotional regulation and control strategies. However, further empirical support is needed to understand how these traits simultaneously influence each other. Thus, this study aimed to investigate the relationship between the Dark Triad, emotion dysregulation strategies, and locus of control using a predictive model. The participants consisted of 305 individuals aged 18 to 59 years (M = 32.5; SD = 12.05) who responded to the Dirty Dozen (DD), the Emotional Dysregulation Scale (EDEA), the Locus of Control Scale (ELOCUS), and the Baptist Depression Scale (EBADEP). Our results suggest positive associations of Machiavellianism, psychopathy, and narcissism with maladaptive emotional dysregulation strategies, and these strategies predicted external locus of control. Therefore, individuals with darker traits tend to employ dysfunctional emotion regulation strategies and consequently attribute external events as the cause of such outcomes.